GE_GERICHTE P/16783/2022 vom 29. April 2024 - GE Cour de justice (2024)
IN DUBIO PRO REO;LÉGITIME DÉFENSE;EXPULSION(DROIT DES ÉTRANGERS);TENTATIVE(DROIT PÉNAL);MEURTRE;PROPORTIONNALITÉ;LÉSION CORPORELLE GRAVE | CP.66a; CPP.10; CP.111; CP.22; CP.15; CP.16; CP.123.ch2